1970
DOI: 10.3126/nepjoph.v3i2.5262
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of fungal isolates in cases of corneal ulcer in the western periphery of Nepal

Abstract: Purpose: To find out the epidemiologic features in 686 consecutive cases of fungal keratitis presenting in a tertiary eye hospital in the western region of Nepal. Materials and methods:A prospective hospital -based study was carried out on 1880 consecutive patients presenting with corneal ulcer in the outpatient department and cornea clinic of Lumbini Eye Institute, Bhairawa, Nepal. The socio-demographic data, predisposing risk factors, prior treatment modalities, laboratory results and the distribution patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 0 publications
2
21
2
Order By: Relevance
“…Our study correlates well with a similar study done in Nepal earlier in the western peripheral terrain belt of Nepal and Indo-Nepal border 24 Ghana and southern India. 25 Where 32% and 39.9 % of cases were due to fusarium species respectively.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…Our study correlates well with a similar study done in Nepal earlier in the western peripheral terrain belt of Nepal and Indo-Nepal border 24 Ghana and southern India. 25 Where 32% and 39.9 % of cases were due to fusarium species respectively.…”
supporting
confidence: 80%
“…The higher incidence of fusarium species may be due to the widespread cereal-crop cultivation in this region. 24 Curvularia species were found to be more prevalent in our study (17.89 %) than in the study done in Ghana and Southern India in which the prevalence was 9.6 %. 22 In a similar study from Nepal 24 curvularia species were found to be more prevalent, which correlated well with this study.…”
contrasting
confidence: 53%
See 3 more Smart Citations